Influence of Phosphoric Acid Modification on Catalytic Properties of γ-χ Al2O3 Catalysts for Dehydration of Ethanol to Diethyl Ether - Mutjalin Limlamthong; Nithinart Chitpong; Bunjerd Jongsomjit (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
In this present work, diethyl ether, which is currently served as promising alternative fuel for diesel engines, was produced via catalytic dehydration of ethanol over H3PO4-modified g-c Al2O3 catalysts. The impact of H3PO4 addition on catalytic performance and characteristics of catalysts was investigated. While catalytic dehydration of ethanol was performed in a fixed-bed microreactor at the temperature ranging from 200ºC to 400ºC under atmospheric pressure, catalyst characterization was conducted by inductively coupled plasma (ICP), X-ray diffraction (XRD), N2 physisorption, temperature-programmed desorption of ammonia (NH3-TPD) and thermogravimetric (TG) analysis. The results showed that although the H3PO4 addition tended to decrease surface area of catalyst resulting in the reduction of ethanol conversion, the Al2O3 containing 5 wt% of phosphorus (5P/Al2O3) was the most suitable catalyst for the catalytic dehydration of ethanol to diethyl ether since it exhibited the highest catalytic ability regarding diethyl ether yield and the quantity of coke formation as well as it had similar long-term stability to conventional Al2O3 catalyst. The NH3-TPD profiles of catalysts revealed that catalysts containing more weak acidity sites were preferred for dehydration of ethanol into diethyl ether and the adequate promotion of H3PO4 would lower the amount of medium surface acidity with increasing catalyst weak surface acidity. Nevertheless, when the excessive amount of H3PO4 was introduced, it caused the destruction of catalysts structure, which resulted in the catalyst incapability due to the decrease in active surface area and pore enlargement.